A real-time resolution independent animation viewer - Ong, Remus Hong Han. (2013)
CACANi (Computer Assisted Cel Animation) is an animation system developed by Nanyang Technological University’s School of Computer Engineering. With this animation system, animators need only to draw main keyframes, allowing the system to automatically generate as many in-between frames necessary to create a smooth sequence. The existing application uses a loosely organized file importer and exporter. Hence, it is difficult to tell what values the numbers in the saved files correspond to, especially when new attributes are being introduced or reorganized.